Current‐Dependent Lithium Metal Growth Modes in "Anode‐Free" Solid‐State Batteries at the Cu|LLZO Interface. Issue 1 (7th November 2022) - Fuchs, Till; Becker, Juri; Haslam, Catherine G.; Lerch, Christian; Sakamoto, Jeff; Richter, Felix H.; Janek, Jürgen
Abstract: Controlling the lithium growth morphology in lithium reservoir‐free cells (RFCs), so‐called "anode‐free" solid‐state batteries, is of key interest to ensure stable battery operation. Despite several benefits of RFCs like improved energy density and easier fabrication, issues during the charging of the cell hinder the transition from lithium metal batteries with a lithium reservoir layer to RFCs. In RFCs, the lithium metal anode is plated during the first charging step at the interface between a metal current collector and the solid electrolyte, which is prone to highly heterogeneous growth instead of the desired homogeneous film‐like growth. Herein, the lithium morphology during the first charging step in RFCs is explored as a function of current density and current collector thickness. Using operando scanning electron microscopy, an increase in the lithium particle density is observed with increasing current density at the Cu|Li6.25 Al0.25 La3 Zr2 O12 interface. This observation is then applied to improve the area coverage of lithium by pulsed plating. It is also shown that thin current collectors ( d  = 100 nm) are unsuited for RFCs, as lithium whiskers penetrate them, resulting in highly heterogeneous interfaces. This suggests the use of thicker metal layers (several µm) to mitigate whisker penetration and facilitate homogeneous lithium plating. Abstract : This work demonstrates a novel operando scanning electron microscopy (SEM) technique to visualize the lithium growth at the Cu|LLZO interface within so‐called "anode‐free" cell designs. Detailed SEM and image analysis shows a clear dependence of the growth morphology on applied current density and current collector thickness.